Лирика Я. П. Полонского(The Poetry of Jakov Polonskij) - Egeberg, Erik (Poljarnyj vestnik, 2002)
In this article the poetry of Jakov Polonskij is compared to Afanasij Fet's verse with a special focus on the motif "night". A juxtaposition of par- allel passages demonstrates both similarities and profound differences: on the one hand, Polonskij is familiar with the various aspects of verse technique so brilliantly applied by Fet, while on the other hand he avoids the erotically coloured emotional climax which often concludes Fet's poems. In Polonskij a joyful mood is combined with dissonant notes of doubt and disillusion.
Keywords: Russian; literature; poetry; Jakov Polonskij